Sustainable Food Production and Strategic Management - ZAURE, Salzhanova; KUANYSH, Ayazhanov; MUKASHEVA, Gulzhan; ZHANNA, Arynova; YESBOLGANOVA, Gaukhar (Journal of Environmental Management and Tourism; Vol 9 No 1 (2018): JEMT Volume IX Issue 1(25) Spring 2018, 2018)
These days, sustainability is a key issue for many private companies that address their sustainable corporate performance. The perspective is essential for their license to operate and forms the basis for business principles and practices. The lack of internationally accepted reporting standards on what, when and where to report makes it difficult to assess sustainability. The article examines different sustainable methods to forecast the development of food sector in Kazakhstan. The scenario approach is used as the most effective one that, in the authors’ opinion, allows taking into consideration a variety of tendencies in the sphere of production, distribution and consumption of food products. Kazakhstan has real opportunities to produce a wide range of food products in the volume, that ensure not only food security of the country, but also the possibility of expanding the export potential of Kazakhstan both at the expense of raw materials and the realization of food products on the world markets with high added value. Currently, however, the food potential of the country is being used inefficiently.